ANALISIS PROVISIONAL MEASURES ICJ ATAS KASUS DUGAAN GENOSIDA DI GAZA: STUDI KASUS SENGKETA AFRIKA SELATAN V. ISRAEL - Sirtufillaeli; Muh Risnain; Diva Pitaloka (Mataram Journal of International Law, 2025)
This study aims to examine the legal considerations of the International Court of Justice (ICJ) in issuing provisional measures and their impact on the situation in Gaza. The research employs a normative legal method with a case study approach, focusing on the South Africa v. Israel dispute and relevant international treaties. The legal materials used in this research include both primary and secondary sources, collected through library research. The ICJ established that it had prima facie jurisdiction and issued an order for provisional measures on 26 January 2024, which was subsequently reinforced by additional orders on 28 March and 24 May 2024. These measures were grounded in the need to protect certain rights that were plausibly at risk, the link between those rights and the requested measures, and the potential for irreparable harm if urgent action was not taken. In these orders, Israel was instructed to prevent acts that could be classified as genocide and to preserve evidence. Provisional measures issued by the ICJ are binding in nature, as affirmed in paragraph 109 of the Court's 2001 LaGrand case judgment. However, while binding, such measures are not enforceable in the sense that the ICJ lacks coercive authority to compel state compliance. Moreover, the presence or absence of specific intent (dolus specialis) is crucial in determining whether acts constitute genocide. Even if acts meet the threshold of international crimes, without this specific intent, they may not be classified as genocide.